Design and evaluation of new majority gate-based RAM cell in quantum-dot cellular automata. Issue 1 (January 2015) - Angizi, Shaahin; Sarmadi, Soheil; Sayedsalehi, Samira; Navi, Keivan
Abstract Quantum-dot cellular automata is one of the candidate technologies used in Nano scale computer design and a promising replacement for conventional CMOS circuits in the near future. Since memory is one of the significant components of any digital system, designing a high speed and well-optimized QCA random access memory (RAM) is a remarkable subject. In this paper, a new robust five-input majority gate is first presented, which is appropriate for implementation of simple and efficient QCA circuits in single layer. By employing this structure, a novel RAM cell architecture with set and reset ability is proposed. This architecture has a simple and robust structure that helps achieving minimal area, as well as reduction in hardware requirements and clocking zone numbers. Functional correctness of the presented structures is proved by using QCADesigner tool. Simulation results confirm efficiency and usefulness of the proposed architectures vis-à-vis state-of-the-art.